Microbiota de ninhos de espuma no combate à quitridiomicose: estratégias para conservação de anfíbios - Sousa, Paulo Ricardo Santos de (2024)
Anurans are the vertebrates experiencing the highest population decline globally, with chytridiomycosis caused by the pathogenic fungus Batrachochytrium dendrobatidis (Bd) reported as the primary cause of this decline. It has been reported that the skin microbiota of anurans plays a crucial role in controlling Bd. These bacteria are considered a promising strategy for the development of probiotics that strengthen the host's defenses, preventing chytridiomycosis. Foam nests are biofoams composed of ranaspumin proteins and carbohydrates that provide shelter for eggs until they develop into tadpoles. Similar to anuran skin, foam nests have a unique microbiota, yet unexplored for the presence of anti-Bd bacteria. Thus, this research aimed to prospect anti-Bd bacteria in foam nests of the frog species Adenomera hylaedactyla, Leptodactylus vastus, and Physalaemus cuvieri, aiming to identify potential isolates that can act in controlling the pathogen during the early stages of tadpole development. The study evaluated 182 bacterial isolates from nests of the three frog species. Anti-Bd activity was assessed directly by inoculating the test bacteria at equidistant points on the surface of 1% Tryptone Agar plates containing a standardized Bd layer. Results were analyzed based on the presence or absence of inhibition halos around the isolates. To assess if the activity was due to an extracellular product, each test bacterium's culture was co-cultivated with the fungus, and the co-culture supernatant was cultured in liquid medium inoculated with a standardized Bd suspension. The result was expressed by the number of viable total Bd. Based on the results of the two tests and the compatibility test among the isolates, 11 candidates were selected to form an anti-Bd probiotic consortium from the 55 with hability to inhibit Bd growth. The isolates were combined in18 different consortia. As a result, 30.77% of the isolates were capable of directly inhibiting Bd growth, while only 4.95% of the culture supernatants showed significant Bd inhibition. Additionally, 64.84% of the culture supernatants stimulated Bd growth. In both tests, the most promising isolates with anti-Bd activity were belonging to the genus Pseudomonas. Thirteen of the eighteen consortia showed moderate inhibition. Five consortia stood out, composed of bacteria belonging to the genera Aeromonas, Acinetobacter, Chryseobacterium, Microbacterium, Pseudomonas, and Serratia. The results of this study demonstrate that components of the microbiota in frog foam nests may be the key to Bd control in the early developmental stages. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001.